Promise program design for equity outcomes: A landscape survey - Michelle Miller-Adams; Isabel McMullen (W.E. Upjohn Institute for Employment Research, 2022)
Using the W.E. Upjohn Institute's Promise Programs Database - a searchable data set covering about 200 place-based scholarship programs-this paper explores how the design of Promise programs can shape their equity impacts. The authors first examine the landscape of place-based programs to understand the impact of program design on equity outcomes. They then use the statistical method of polychoric correlation to combine design features related to the equity potential of community-based Promise programs and develop an index expressing this concept. They conclude with two vignettes of recently announced Promise programs with different design features and implementation strategies to highlight the varied paths to equitable student outcomes. The paper finds that while some Promise programs have more potential than others to close equity gaps, whether they in fact do so will depend on implementation. Ongoing definitional debates, program heterogeneity, and the difficulty of observing implementation all complicate the task of assessing equity impact and underscore the need for more qualitative research focused on questions of equity and effectiveness.
Keywords: I22; I24; 330; Free college; Promise programs; College Promise; Education equity; Place-based scholarship; Tuition-free higher education